1999
DOI: 10.4314/cajm.v45i2.8447
|View full text |Cite
|
Sign up to set email alerts
|

Haematologic features of the Human Immunodefiency Virus (HIV) infection in adult Zimbabweans

Abstract: Objective: To describe the haematologic features of the HIV infection in adult Zimbabweans and compare the features in the different clinical stages of the disease. Design: Descriptive cross sectional study. Setting: Parirenyatwa Hospital, a tertiary and referral medical centre in Harare, and the blood donor clinics of the Blood Transfusion Service in Harare. Subjects: Patients attending HIV outpatients clinics or receiving inpatient care at Parirenyatwa Hospital and asymptomatic persons donating blood at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 3 publications
(3 reference statements)
3
33
1
Order By: Relevance
“…[27][28][29][30] In this study, we found that half of ARV-naive Asian children without advanced HIV had anemia. Most anemic children had a mild degree of anemia.…”
Section: Discussionmentioning
confidence: 77%
“…[27][28][29][30] In this study, we found that half of ARV-naive Asian children without advanced HIV had anemia. Most anemic children had a mild degree of anemia.…”
Section: Discussionmentioning
confidence: 77%
“…A study conducted among adult Zimbabweans showed that the prevalence of leukopenia and of thrombocytopenia was 11.7% and 24.7%, respectively (13). Leukopenia and thrombocytopenia were seen in 26.8% and 21.7% of HIV patients with CD4 counts less than 200 cells/mm 3 in India, respectively (14).…”
Section: Discussionmentioning
confidence: 99%
“…1 The higher anemia rates among HIV-infected individuals in southern Africa, compared with similar patients in the United States, make hematopoiesis and HIV-1C's effect on progenitor cell health an important area of investigation. [2][3][4] Recent findings by our group demonstrated that HIV-1 infection was directly associated with hematopoiesis in HIV-infected patients in Botswana, a country in southern Africa. 5 The study found direct positive associations between CD4 Ļ© and CD34 Ļ© cell levels, and between CD34 Ļ© /CD4 Ļ© dual-positive cell levels and both hemoglobin counts and colony-forming ability, as well as negative correlations between circulating viral levels and all indicators of HIV infection and hematopoietic health tested.…”
Section: Introductionmentioning
confidence: 99%